2006
DOI: 10.1016/j.soilbio.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community composition as affected by restoration practices in California grassland

Abstract: Agricultural practices have strong impacts on soil microbes including both the indices related to biomass and activity as well as those related to community composition. In a grassland restoration project in California, where native perennial bunchgrasses were introduced into non-native annual grassland after a period of intensive tillage, weeding, and herbicide use to reduce the annual seed bank, microbial community composition was investigated. Three treatments were compared: annual grassland, bare soil fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(79 citation statements)
references
References 56 publications
6
70
1
2
Order By: Relevance
“…This is not unexpected given that microbial biomass and total PLFA have been found to be highly correlated with each other (Potthoff et al 2006). As in a previous study, PLFA analysis showed little difference in soil microbial communities between the two tomato genotypes (Cavagnaro et al 2006).…”
Section: Discussionsupporting
confidence: 84%
“…This is not unexpected given that microbial biomass and total PLFA have been found to be highly correlated with each other (Potthoff et al 2006). As in a previous study, PLFA analysis showed little difference in soil microbial communities between the two tomato genotypes (Cavagnaro et al 2006).…”
Section: Discussionsupporting
confidence: 84%
“…The composition and activity of the soil microbial community is influenced by ecosystem state factors (e.g., climate, soil type), plant species composition and, farming practices in agroecosystems [9][10][11]. Organic management practices using diverse rotations and additions of organic residues affect microbial community structure over the long term through buildup of soil organic matter (SOM) and changes in SOM chemistry [6,7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Organic management practices using diverse rotations and additions of organic residues affect microbial community structure over the long term through buildup of soil organic matter (SOM) and changes in SOM chemistry [6,7,[12][13][14]. In addition, greater crop diversity alters plant litter inputs and can presumably increase the number of ecological niches available for soil microbes [7,11]. The structure of microbial communities can in turn have important implications for the rates of soil processes.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions and perturbations are likely to affect population structures and their functions in soils which may in turn result in a change of overall soil properties (Widmer et al, 2000). Understanding the microbial ecology of soil is increasingly recognized as important for the restoration and sustainability of ecosystems (Steenwerth et al, 2002;Potthoff et al, 2006). Soil microbial parameters are probably the earliest indicators of soil quality used.…”
Section: Introductionmentioning
confidence: 99%